Supply chain flexibility: A comprehensive review - Tiwari A.K.; Tiwari A.; Samuel C. (My University, 2025)
Purpose – Changes are inevitable in risky and uncertain business environments of today’s volatile supply chains. The concept of flexibility originates from this need to mitigate the ill-effects of risks and uncertainty in supply chains. In this paper, an attempt is made to present an exhaustive review on supply chain flexibility (SCF) and its implementation to gain strategic advantages. Design/methodology/approach – A citation analysis method is employed in this paper to discuss, analyse and apprehend the conceptual, empirical, analytical and simulation studies done in this field. In this paper, about 110 papers on flexibility from many reputed journals are examined to study and assimilate various aspects of flexibility. Findings – SCF embraces a unified process-based view including the core processes such as procurement, sourcing, distribution and logistics and mitigates uncertainty or risks involved. The review helps to assimilate the key knowledge about relevant practices in SCF and helps to draw implementing strategies while offering managerial insight on the subject. Research limitations/implications – Citation and co-citation analysis is done to review the SCF literature. Efforts are made to investigate relevant papers from various journals regarding its ability to mitigate risk or aid in making strategic decision. The study, however, is limited to certain industries in the papers as per chosen approach here. The strategies described in here may further be verified by the researchers and practitioners pertaining to their study or industries focused. Practical implications – It provides managerial insight for practitioners on how to use flexibility within the firm and across supply chain while considering various trade-offs. Originality/value – This paper is unique as a review paper, as it encompasses various kinds of studies done on SCF from conceptual models to mathematical models. Further, it briefs with the current practices in industries/SC towards being flexible. It talks of various trade-offs in pursuit of flexibility and concludes while suggesting numerous research gaps and opening new dimensions for SCF research. It offers many managerial and academic implications. © Emerald Group Publishing Limited.